Corporate governance and corporate environmental investments: Evidence from China. Issue 6 (September 2020) - Li, Qiang; Ruan, Wenjuan; Sun, Tiantian; Xiang, Erwei
Using a data set of Chinese listed companies over the period 2008 to 2015, this paper empirically examines whether corporate governance affects the environmental investment decisions. We find that the separation of controlling shareholder's control right and cash flow right is negatively correlated to corporate environmental investment. Moreover, managerial ownership strengthens the abovementioned negative correlation, which is consistent with the controlling shareholder–manager collusion hypothesis. A further test suggests that internal control effectively weakens the controlling shareholder–manager collusion in their environmental investment decisions.